Circulating Forms of B-Type Natriuretic Peptide in Very Preterm Infants. (25th February 2020) - Harris, Sarah L; Troughton, Richard; Lewis, Lynley; Austin, Nicola; Pemberton, Chris
Abstract: Background: B-type natriuretic peptide (BNP) is a cardiac hormone released with an N-terminal fragment (NTproBNP) under conditions of ventricular pressure or volume overload. BNP has been proposed for use as a biomarker of cardiac dysfunction in premature infants in the setting of hemodynamically significant patent ductus arteriosus (HsPDA) and bronchopulmonary dysplasia (BPD). In adult settings the presence of proBNP and glycosylated isoforms may affect assay interpretation. However, there are limited data on how immature preterm physiology may affect BNP or NTproBNP levels and no published data on post-translational BNP processing in premature infants. Methods: Pooled serial plasma samples from preterm infants born at less than 30 weeks gestation were analyzed for BNP congeners using Luminex ® assay and high performance liquid chromatography. Samples were grouped according to clinical status: Group 1, no HsPDA and no BPD, Group 2 HsPDA and no/mild BPD, Group 3 HsPDA and moderate/severe BPD. Results: Plasma from 15 infants was analyzed, and across all three groups NTproBNP predominated with minimal amounts of other isoforms; no glycosylation was detected. Conclusions: NTproBNP appears to be the predominant isoform across each of our clinical groups in our pooled sample analysis with no evidence of significant glycosylation. This suggests NTproBNP is likely to be a robust marker in this clinical setting.